Bacterial diversity in Malan ice core from the Tibetan Plateau - Xiang, S R; Yao, T D; An, L Z; Xu, B Q; Li, Z; Wu, G J; Wang, Y Q; Ma, S; Chen, X R (Folia microbiologica, 2004)
Three ice core samples were collected from the Malan ice core drilled from the Tibetan Plateau, and three 16S rDNA clone libraries by direct amplification from the ice-melted water were established. Ninety-four clones containing bacterial 16S rDNA inserts were selected. According to restriction fragment-length polymorphism analysis, 11 clones were unique in the library from which they were obtained and used for partial sequence and phylogenetic analysis, and compared with 8 reported sequences from the same ice core at depth 70 m. Differences among the samples were apparent in clone libraries. The phylotypes were dominated by the Proteobacteria group, Acinetobacter sp. and Cytophaga-Flavobacterium-Bacteroides (CFB) group. They accounted for 92.5% (Proteobacteria), 100% (Acinetobacter sp.), 34.4% (CFB) and 100% (beta-Proteobacteria) in the clone libraries from the samples at ice depths 35, 64, 70, and 82 m, respectively. The Acinetobacter sp. was only found in the deposition at ice depth 82 m and closely clustered with gamma-Proteobateria. Two members (Malan A-21 and 101) of alpha-Proteobacteria from the sample of 35 m and two (Malan B-26 and 48) of beta-Proteobacteria of 64 m were loosely clustered (< 95% similarity) with known bacteria, represented new genera in ice bacteria.
Keywords: Bacteria; led; DNA, Ribosomal; RNA ribozomální 16S; Geologic Sediments; Tibet; Ice; Water Microbiology; mikrobiologie vody; RNA, Ribosomal, 16S; ribozomální DNA; geologické sedimenty